Analysis of the Influence of Work Effectiveness and Culture Work on Employee Performance at PT. Widya Techno Abadi Medan - Victor Victor; Denni Denni; Viona Anggara (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to describe the influence of work effectiveness and work culture on employee performance at PT. Widya Techno Abadi Medan. This research was conducted for 6 (Six) months, starting from October 2023 to March 2024. This research used a non-probability sampling method, namely census sampling. The respondents of this research are employees at PT. Widya Techno Abadi Medan, numbering 40 (forty) people. The instrument used is a questionnaire to collect data from work effectiveness variables, work culture variables and employee performance variables. The data analysis techniques used are validity test, reliability test, descriptive analysis, normality test, multiple linear regression analysis, partial hypothesis test or t test and calculation of the coefficient of determination. Determining the results of descriptive analysis for work effectiveness variables, work culture variables and employee performance variables are in the very good category. Based on partial analysis, work effectiveness and work culture have a positive and significant effect on employee performance at PT. Widya Techno Abadi Medan. Based on a simultaneous analysis of work effectiveness and work culture, it has a positive and significant effect on employee performance at PT. Widya Techno Abadi Medan.